The Four seam Trawl Nets Operated Off Cochin-An Analysis of the Design Aspects - the Integration of the Various Parts of Trawl - Nair, R S; George, N A (Fishery Technology, 1964)
A study has been made of 22 different designs of four seam trawls operated at Cochin for shrimp trawling. Formulae for the relations between the different parts of the nets have been derived.